Long-term weight change and breast cancer risk: the European prospective investigation into cancer and nutrition (EPIC). - Lahmann, P; Schulz, M; Hoffmann, K; Boeing, H; Tjønneland, A; Olsen, A; Overvad, K; Key, T; Allen, N; Khaw, K; Bingham, S; Berglund, G; et al. (2005)
We examined prospectively the association between weight change during adulthood and breast cancer risk, using data on 1358 incident cases that developed during 5.8 years of follow-up among 40,429 premenopausal and 57,923 postmenopausal women from six European countries, taking part in the European prospective investigation into cancer and nutrition study. Multivariate Cox regression models were used to calculate hazard ratios according to weight change (kg), defined as the weight difference between age at enrollment and age 20 adjusted for other risk factors. Changes in weight were not associated with premenopausal breast cancer risk. In postmenopausal women, weight gain was positively associated with breast cancer risk only among noncurrent hormone replacement therapy (HRT) users (P-trend < or = 0.0002). Compared to women with a stable weight (+/-2 kg), the relative risk for women who gained 15-20 kg was 1.50 (95% confidence interval (CI) 1.06-2.13). The pooled RR per weight gain increment of 5 kg was 1.08 (95% CI 1.04-1.12). Weight gain was not associated with breast cancer risk in current HRT users, although, overall, these women experienced a much higher risk of breast cancer compared with nonusers. Our findings suggest that large adult weight gain was a significant predictor of breast cancer in postmenopausal women not taking exogenous hormones.